1991
DOI: 10.1007/bf00010407
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus efficiency of plants

Abstract: F6hse et al. (1988) have shown that P influx per unit root length in seven plant species growing in a low-P soil varied from 0.6 × 10 -14 to 4.8 × 10 -14 mol cm-ls -1. The objective of this work was to investigate the reasons for these differences. No correlation was found between P influx and root radius, root hairs, cation-anion balance and Ca uptake. However, when root hairs were included in mathematical model calculations, the differences of P influx could be accounted for. These calculations have shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
7

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(43 citation statements)
references
References 32 publications
(13 reference statements)
2
32
0
7
Order By: Relevance
“…In barley (Brown et al, 2012) and maize (Zhu et al, 2010), low P availability induces an increase in RH length, which is assumed to boost the efficiency of P uptake (Haling et al, 2013). Under P-limiting conditions, up to 90% of the mineral appears to be taken up by the RHs in different plant species (Fohse et al, 1991), a proportion that readily explains the major difference in the P acquisition capacity between barley accessions that form short as opposed to long RHs (Gahoonia and Nielsen, 2004;Brown et al, 2012). The importance of RHs for both cadmium and zinc acquisition has been illustrated by comparing the performance of the barley root-hairless mutant bald root barley (brb) with that of its parent cv Pallas.…”
mentioning
confidence: 99%
“…In barley (Brown et al, 2012) and maize (Zhu et al, 2010), low P availability induces an increase in RH length, which is assumed to boost the efficiency of P uptake (Haling et al, 2013). Under P-limiting conditions, up to 90% of the mineral appears to be taken up by the RHs in different plant species (Fohse et al, 1991), a proportion that readily explains the major difference in the P acquisition capacity between barley accessions that form short as opposed to long RHs (Gahoonia and Nielsen, 2004;Brown et al, 2012). The importance of RHs for both cadmium and zinc acquisition has been illustrated by comparing the performance of the barley root-hairless mutant bald root barley (brb) with that of its parent cv Pallas.…”
mentioning
confidence: 99%
“…Some researchers have also found that P or other nutrient efficiency can be achieved by uptake or utilization efficiency (Clark, 1983;Gabelman and Gerloff, 1983;Föhse et al, 1988;Sattelmacher et al, 1994). Other researchers have observed that at high P supply, P efficiency was more favored by a high P uptake, Table 6 Phosphorus uptake and utilization efficiency of wheat genotypes at the shooting stage in the pot experiment P concentration P uptake P-utilization efficiency mg g whereas in P-deficiency conditions it was likely explained by a high internal P-utilization efficiency (Stelling et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Tais diferenças têm sido relacionadas, basicamente, à eficiência com que as plantas absorvem o nutriente da solução e/ou utilizam-no internamente (FURLANI et al, 1985;FÖHSE et al, 1988;JONES et al, 1992). Vários fatores distinguem a capacidade de absorção de fósforo entre genótipos.…”
Section: Introductionunclassified